2006
DOI: 10.1103/physrevlett.97.227001
|View full text |Cite
|
Sign up to set email alerts
|

Strong and Complex Electron-Lattice Correlation in Optimally DopedBi2Sr2CaCu2O8+δ

Abstract: We discuss the nature of electron-lattice interaction in optimally doped Bi_{2}Sr_{2}CaCu_{2}O_{8+delta} samples, using the isotope effect (IE) in angle resolved photoemission spectroscopy (ARPES) data. The IE in the ARPES linewidth and the IE in the ARPES dispersion are both quite large, implying a strong electron-lattice correlation. The strength of the electron-lattice interaction is "intermediate," i.e., stronger than the Migdal-Eliashberg regime but weaker than the small polaron regime, requiring a more g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 34 publications
4
25
1
Order By: Relevance
“…[7][8][9][10][11] In case of doped LaFeAsO system, similar behavior is found in both As and Fe K edge EXAFSs. We note that this distortion is of electronic origin and is different from crystallographic phase transition, as it is observed only after carrier doping at low temperature.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…[7][8][9][10][11] In case of doped LaFeAsO system, similar behavior is found in both As and Fe K edge EXAFSs. We note that this distortion is of electronic origin and is different from crystallographic phase transition, as it is observed only after carrier doping at low temperature.…”
Section: Resultssupporting
confidence: 69%
“…6 On the other hand, various anomalous lattice effects have recently been observed in cuprates which closely correlate with the onset of superconducting transition, suggesting that lattice effects play an important microscopic role in the superconducting pairing mechanism. [7][8][9][10][11][12] In particular, extended x-ray absorption fine-structure ͑EXAFS͒ measurements have shown that doping causes local lattice distortion which occurs well above T c . 7,8,11 Correlating data from inelastic neutron scattering and inelastic x-ray scattering, isotope effects, Raman spectroscopy, infrared-absorption spectroscopy, and femtosecond optical spectroscopy have been proving that the anomalous local lattice distortion observed by EXAFS measurements is correlated with the opening of pseudogap and the formation of polarons.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, though the isotope effect in cuprates ͑if any͒ is much smaller than the one observed in standard ͑i.e., low temperature͒ superconductors, there are experiments suggesting a strong coupling between electrons and localized lattice vibrations. 2,3 On the other hand, besides a clear experimental outcome showing unusual behaviors in both metallic and superconducting phases, there is increasing theoretical evidence that purely electronic models can, indeed, sustain a robust pairing, possibly leading to a high critical temperature. [4][5][6] Within the latter scenario, the minimal microscopic model to describe the low-energy physics has been proposed to be the Hubbard model or its strongcoupling limit, namely, the t-J model, which includes an antiferromagnetic coupling between localized spins and a kinetic term for the hole motion.…”
Section: Introductionmentioning
confidence: 97%
“…This problem has recently received a renewed attention, after a number of experiments on high-T c superconducting cuprates testified for a non trivial role of the e-ph coupling in the underdoped region, where correlation effects are important and standard e-ph theories are hardly reliable 3,4,5,6,7 . Indeed a full theoretical understanding of lattice effects in strongly-correlated systems is still lacking when the two interactions have intermediate or large strength.…”
Section: Introductionmentioning
confidence: 99%